''Two-Week Waits''—Are They Leading to Earlier Diagnosis of Soft-Tissue Sarcomas?. (13th September 2010) - Taylor, W. St. J.; Grimer, R. J.; Carter, S. R.; Tillman, R. M.; Abudu, A.; Jeys, L.
Abstract : Introduction . The ''two-week wait'' was established as a potential means of diagnosing malignant tumours earlier. This paper investigated whether these clinics are leading to earlier diagnosis of malignant soft-tissue lumps. Method . We identified all referrals to our centre from a database over a 4-year period. Results . 2225 patients were referred to our unit for investigation of a soft-tissue mass. 576 (26%) were referred under the ''two-week wait'' criteria. 153 (27%) of which were found to have a malignant or borderline malignant diagnosis. 1649 patients were referred nonurgently. 855 (52%) of which were diagnosed with a malignant or borderline lesion. The average size at diagnosis was 9.4 cm with no difference in size between the different referral routes. Conclusion . There is little evidence that the two-week wait clinic is leading to earlier diagnosis of soft-tissue sarcomas with the majority still being referred nonurgently.